Finite element analysis for oil palm fruit using open-ended coaxial sensor - You, Kok Yeow; Abbas, Zulkifly; Mohd Atan, Kamel Ariffin; Nik Long, Nik Mohd Asri; Hassan, Jumiah; Shaari, Abdul Halim (Institute for Mathematical Research, Universiti Putra Malaysia, 2008)
This paper presents a new technique of predicting the reflection coefficient of a microwave sensor for oil palm fruits using finite element method (FEM). Comparison results between measured and calculated reflection coefficient were found to be in good agreement with magnitude and phase errors of less than 0.05 and 0.2 radian.